Diabetes Technology Meeting 2020. (July 2021) - Shang, Trisha; Zhang, Jennifer Y.; Bequette, B. Wayne; Raymond, Jennifer K.; Coté, Gerard; Sherr, Jennifer L.; Castle, Jessica; Pickup, John; Pavlovic, Yarmela; Espinoza, Juan; Messer, Laurel H.; Heise, Tim; et al.
Diabetes Technology Society hosted its annual Diabetes Technology Meeting on November 12 to November 14, 2020. This meeting brought together speakers to cover various perspectives about the field of diabetes technology. The meeting topics included artificial intelligence, digital health, telemedicine, glucose monitoring, regulatory trends, metrics for expressing glycemia, pharmaceuticals, automated insulin delivery systems, novel insulins, metrics for diabetes monitoring, and discriminatory aspects of diabetes technology. A live demonstration was presented.